Diosmetin Delays In Vitro Aging of Porcine Oocytes by Improving Mitochondrial Function and Reducing Oxidative Stress - Jia-Jun Ren; Xiu-Wen Yuan; Yu-Hao Zhang; Zi-Long Meng; Xing-Wei Liang; Nam-Hyung Kim; Yong-Nan Xu; Ying-Hua Li (Animals)
Oocyte quality is crucial for successful fertilization and subsequent embryonic development. Post-ovulatory aging leads to reduced oocyte quality and impaired embryogenesis, representing an unavoidable challenge in terms of certain assisted reproductive techniques. Diosmetin (DIOS), a natural flavonoid found in lemons, spearmint, and spider moss, exhibits antioxidant, anti-inflammatory, and anti-apoptotic properties. However, its effects on the aging of mature porcine oocytes in vitro remain unexplored. This study investigated the impact of DIOS on porcine oocyte aging. In the IVM medium, fresh oocytes were cultured for 44 h, while aging oocytes were cultured for 68 h. Following the addition of varying DIOS concentrations (0.01, 0.1, and 1 μM) to the IVM medium, the DIOS-treated aging oocyte group was cultured for 68 h. The results demonstrated that 0.1 μM DIOS significantly improved the blastocyst rates and cell counts, reduced the reactive oxygen species (ROS), elevated the glutathione (GSH) levels, enhanced the mitochondrial function, and decreased the markers of autophagy (LC3B), apoptosis (annexin V), endoplasmic reticulum stress (CHOP), and senescence (SA-β-Gal). Furthermore, DIOS treatment upregulated the expression of relevant genes compared to the aged group. These findings suggest that DIOS effectively delays porcine oocyte aging.